A Microprocessor Controlled Population Counter - Kafumbe, Said M. M.; Kundaeli, H.N; Aldalaien, Muawya (Universal Journal of Electrical and Electronic Engineering, 2014)
In this technological era, there exists a growing need for pre-programmed interactive systems that ease day to day activities. Systems that utilise microprocessor-based operations to control other systems are based on coded instructions depicting their actual operation, and can be interfaced to actual systems using both software and hardware techniques. A microprocessor controlled system that can be used in counting the number of biological species in a given environment is presented herein. It uses an 8-bit microprocessor 6502 unit, a pair of infra-red emitters and detectors that can be placed at the entrance, a decade up or down counter as well as a shift register. The optical sensing mechanism detects the entry or exit of the biological species with its output signal amplified and used as an input to an asynchronous sequential combinational digital logic that generates control signals for the up and down counter. The parallel shift register then buffers the maximum count into the microprocessor via the input ports, and with the help of an assembly language code the count is stored into memory and onto the display.
Keywords: Bats; Bio-Population; Decade Counter; Finite State Machines